Unveiling the Familiar: Exploring Makoto Shinkai’s Anime Art - Umme Aiman, (Indian Journal of Social Science and Literature (IJSSL), 2024)
In the past few years, film theory has experienced incredible growth and transformation. In modern film theory, the analysis of the relationship that films have with their recipients is a key area of research. This study examines the aesthetics of Makoto Shinkai’s anime and how it realistically depicts the outside world. Additionally, it will compare and contrast their investigations of this realism in his art style with selections from Shinkai’s corpus of films. Harnessing the principles embedded in the concept of mimesis developed by Walter Benjamin, this paper uses a recipient-centred approach to cinema narrative. This study is significantly central to the art style rather than its structure by observing the characteristics of animation drawings and audio-visual in the anime. The paper provides an insight into the connection between man and man-made, which unveils the familiarity we have with nature—justifying the hypothesis by employing the literary theory of Mimesis. It investigates the art style of Shinkai’s animation that works as a special force to realize this connection. It will enable one to recognize the significance of his works in serving as a model that consciously or unconsciously influences the recipients to take note of and appreciate the mundane sights and moments of life around them.